PENGARUH GAS HIDROGEN SULFIDA (H2S) TERHADAP KELUHAN SUBYEKTIF PETUGAS PENGOLAHAN SAMPAH DI PUSAT DAUR ULANG JAMBANGAN SURABAYA - Istiqomah Farah Novita Devi Suwarno; Rusmiati; Rachmaniyah (Poltekkes Kemenkes Surabaya, 2022)
The Jambangan Recycling Center (PDU) in Surabaya is a waste management site that applies the 3R principles, namely Reuse, Reduce, Recycle. The amount of waste that comes in every day is 5-6 tons. The waste processing officer complained of subjective complaints in the form of influenza, cough, sore throat and chest pain. The purpose of the study was to determine the effect of H2S gas on subjective complaints of waste processing officers at the Jambangan Recycling Center Surabaya. This research is an analytic observational research with a cross sectional approach. This research was conducted at the Jambangan Recycling Center. Sampling of respondents and ambient air was carried out by saturated sampling with a total population and sample of 27 people. Data collection techniques in this study used measurements, observations, and interviews. Data analysis using SPSS application with Spearman Correlation Test. The results showed that the average level of Hydrogen Sulfide (H2S) in the Jambangan Recycling Center Surabaya was 0.00054 ppm which was included in the eligible category according to the East Java Governor Regulation Number 10 of 2009. This study also showed that 27 waste processing officers who 2 people experienced severe complaints, 25 people had mild complaints, and there were no waste processing officers who had no complaints. The conclusion of the study is that there is no effect between levels of Hydrogen Sulfide on subjective complaints of waste processing officers at the Jambangan Recycling Center Surabaya (P = 0.336) so it is recommended to the relevant agencies to monitor air quality regularly. Waste processing officers are also advised to use personal protective equipment when in the Surabaya Jambangan Recycling Center environment.